Design of an Open Source Anthropomorphic Robotic Hand for Telepresence Robot - Jittaboon Trichada; Traithep Wimonrut; Narongsak Tirasuntarakul; Eakkachai Pengwang (Advances in Science, Technology and Engineering Systems Journal, 2023)
Most anthropomorphic robotic hands use a lot of actuators to imitate the number of joints and the movement of the human hand. As a result, the forearm of the robot hand has a large size for the installation of all actuators. This robot hand is designed to reduce the number of actuators, but also retain the number of movable joints like a human hand by using the four-bar linkage mechanism and only flexion-extension movements. This stamen is added in the problem statement according to the reviewer’s comment. The special features of this robotic hand are the ability to adjust the link length and the range of rotation for each joint to suit various applications and can fabricate with 3D printing and standard parts with costing about $750. All hardware CAD files and equations are published on the GitHub website, which benefits for researchers to utilize as an open-source approach that their project might be further expanded in the future. The anthropomorphic robotic hand has five fingers, 16 joints, and 12 active Degrees of Freedom (DOFs) with 12 servo motors applied to finger motion and one for wrist motion. The structure of the hand is designed using the average of Asian human hands in combination with the golden ratio. All servo motors are installed in the forearm designed in a ventilated structure with 12V vent exhaust fan motor to stabilize the operating temperature of the robotic hand. Size and weight of the hand included with the forearm are 20×54×16.5 centimeters and 2.2 kilograms respectively. The hand has achieved human-like movement by using a four-bar linkage mechanism and tendon with PTFE tube to guide operation path of the tendon with the lowest friction force. This paper presents the design processes, the experimental set-up, and the evaluation of the finger movements. From the experiment of grasping objects, this hand was able to grasp 10 basic grasp types including 32 different objects, perform 9 common gestures, and lift the object to 450 grams. From this paper, the kinematic equation is proved that the designed finger structure can move exactly as the equation with maximum error of repeatability test around 1.6 degrees.
Keywords: Open source; Anthropomorphic Robotic Hand; Low cost